Development of Karanda (Carissa carandas L.) Thai Dipping Sauce for Chicken - tubbiyam, prassanee; Manaroje, Apinya (Journal of Food Technology, Siam University, 2022)
The aims of this research were to select the basic recipe and develop Thai dipping sauces for chicken from karanda juice, which was used to replace vinegar at 0, 25, 50, 75 and 100%, respectively. The panelists gave the highest score and accepted Thai dipping sauce for chicken from karanda juice at 100% substitution level, especially the odor and taste scores (p<0.05). The effect of karanda juice used to replace vinegar on the characteristics and qualities of karanda Thai dipping sauce for chicken was also studied. For physical properties, the color of karanda Thai dipping sauce for chicken 100% was darker, due to the color of karanda fruits and viscosity value was higher than basic Thai dipping sauce (p<0.05). For chemical properties, the total soluble solid of karanda Thai dipping sauce for chicken 100% was 64.50±0.01 °Brix, pH value was 2.99±0.03, total acidity was 1.82±0.02%, total phenolic content was 0.75±0.00 mg GEA/g sample and DPPH scavenging radical activity was 6.25±0.00 µmole Trolox/g sample. In addition, karanda juice used to replace vinegar in Thai dipping sauce for chicken was found to have higher carbohydrate content and calorie than basic recipe Thai dipping sauce. Karanda Thai dipping sauce for chicken was safe from pathogens and spoilage microorganisms, which complied with the standard for Thai dipping sauce.